(untitled) (Nigerian Journal of Technology, 2017)
As a result of effect of geographical location on timber properties, there is need for constant determination of properties of timber. This paper presents the results of experimental tests carried out on three Apa (Afzelia bipindensis) timber logs grown in Kwara State, south-western periphery of the North Central Zone of Nigeria in order to ascertain its structural strength properties. Logs of Apa timber were air-dried and along the stem, 324 pieces of test specimens were prepared for determination of their strength properties using a universal testing machine (UTM) FS50AT model, (specimen prepared included 108 samples for tensile strengths parallel to grain, 108 samples for compression parallel to grain and 108 samples for bending parallel to grain) at a moisture content of 12%, in accordance with the Nigerian, British and European standards. The moisture content of 12 % was converted to 18% which is specified in a standard document, for the area. Statistical analysis was carried out using the strength properties for determination of mean, standard deviation, confidence limit and characteristic strength. The result revealed that the timber is satisfactory for structural purposes in construction works.